Evaluasi terhadap Stimulan Ethephon dalam Penyadapan Pinus merkusii (Evaluation on Ethephon Stimulant to Pinus merkusii Tapping) - Lukmandaru, Ganis; Sunarta, Sigit; Listyanto, Tomy; Kasmudjo, Kasmudjo; Pujiarti, Rini; Widyorini, Ragil (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
The aim of this study was to find out the effect of Ethephon, an ethylene releasing compound, in a combination with sulfuric acid resin production Pinus merkusii. The tested stimulants were ETRAT; SR4; 20% sulfuric acid; 20% sulfuric acid - Ethephon 2%; 3.3% sulfuric acid – 4.1% Ethephon; and sulfuric acid – 8.3% Ethephon. Trees without stimulant spraying were the controls. The results showed that for daily production, the first-day observation gave the highest value but decreased drastically after second-day observation in a varied degree depent on the stimulants. On the basis of accumulated production, the addition of Ethephon in a high or low level of sulfuric acid concentration exhibited significantly higher resin production compared to that of ETRAT; SR4; and 20% sulfuric acid stimulants as well as control trees. It increased resin production by 98.0-150.6% compared to control trees in class age of VII and increased by 140.9-227.1% in class age of IV stands. Moderate significant correlations (r=0.65) were observed between the values of resin production and tree diameter (controls) as well as between the values of resin production and tree diameter of trees treated by sulfuric acid stimulants (r=0.65-0.82).Keywords : class age, ethylene, quarre, resin production, tree diameter